Intense Winter Surface Melt on an Antarctic Ice Shelf. Issue 15 (15th May 2018) - Kuipers Munneke, P.; Luckman, A. J.; Bevan, S. L.; Smeets, C. J. P. P.; Gilbert, E.; van den Broeke, M. R.; Wang, W.; Zender, C.; Hubbard, B.; Ashmore, D.; Orr, A.; King, J. C.; et al.
Abstract: The occurrence of surface melt in Antarctica has hitherto been associated with the austral summer season, when the dominant source of melt energy is provided by solar radiation. We use in situ and satellite observations from a previously unsurveyed region to show that events of intense surface melt on Larsen C Ice Shelf occur frequently throughout the dark Antarctic winter, with peak intensities sometimes exceeding summertime values. A regional atmospheric model confirms that in the absence of solar radiation, these multiday melt events are driven by outbreaks of warm and dry föhn wind descending down the leeside of the Antarctic Peninsula mountain range, resulting in downward turbulent fluxes of sensible heat that drive sustained surface melt fluxes in excess of 200 W/m 2 . From 2015 to 2017 (including the extreme melt winter of 2016), ∼23% of the annual melt flux was produced in winter, and spaceborne observations of surface melt since 2000 show that wintertime melt is widespread in some years. Winter melt heats the firn layer to the melting point up to a depth of ∼3 m, thereby facilitating the formation of impenetrable ice layers and retarding or reversing autumn and winter cooling of the firn. While the absence of a trend in winter melt is consistent with insignificant changes in the observed Southern Hemisphere atmospheric circulation during winter, we anticipate an increase in winter melt as a response to increasing greenhouse gas concentration. Plain Language Summary: Around the coast of Antarctica, it gets warm enough in summer for snow to start melting, and the sun provides most of the energy for that melt. Almost all meltwater refreezes in the snowpack, but especially on floating glaciers in Antarctica, it has been observed that meltwater forms large ponds. The pressure exerted by these ponds may have led to ice shelves collapsing into numerous icebergs in recent decades. It is therefore important to understand how much meltwater is formed. To find out, we installed an automatic weather station on a glacier in Cabinet Inlet, in the Antarctic Peninsula in 2014. The station recorded temperatures well above the melting point even in winter. The occurrence of winter melt is confirmed by satellite images and by thermometers buried in the snow, which measured a warming of the snow even at 3 m depth. Between 2014 and 2017, about 23% of all melt in Cabinet Inlet occurred in winter. Winter melt is due to warm winds that descend from the mountains, known as föhn. We have not seen the amount of winter melt increasing since 2000. However, we expect winter melt to happen more frequently if greenhouse gas continues to accumulate in the atmosphere. Key Points: Wintertime surface melt occurs frequently in the Antarctic Peninsula Winter melt heats the firn to a depth of about 3 m, retarding or reversing winter cooling Increased greenhouse gas concentrations could increase the occurrence of winter surface melt